A new record of the genus Calonema, with the new species Calonema gansuence from China - Bo, Zhang; Li, Yu (Phytotaxa, 2015)
The genus Calonema is recorded from China for the first time as the new species Calonema gansuence, described on the basis of material collected from Qilian Mountain, Gansu Province, China. This new species is characterized by its brick brown sporocarps, relatively thick peridium and spores (about 9–12 μm in diam.) marked with rows of warts. A description, scanning electron micrographs and a key to all of the species in the genus Calonema are provided herein. Holotype specimens are deposited in the Herbarium of the Mycological Institute of Jilin Agricultural University (HMJAU), Changchun, China.